The Linguistic Landscape in China Commodification, Image Construction, Contestations and Negotiations - Han, Yanmei; Shang, Guowen (Springer Nature Singapore : Imprint: Springer, 2024)
XIII, 183 p. 50 illus., 48 illus. in color.